Pelaksanaan Pemberian Asimilasi Rumah Bagi Narapidana di Lembaga Pemasyarakatan Kelas II B Sumedang di Tahun 2022 - Mardilana Gautama; Mitro Subroto (Faculty of Law, Diponegoro University, 2022)
Assimilation of homes for inmates who have fulfilled various requirements in accordance with the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 43 of 2021 The Terms and Procedures for Granting Assimilation, Parole, Leave Before Release, and Conditional Leave, for Prisoners and Children in the Framework of Prevention and Countermeasures of Covid-19, aim to integrate inmates or students into the middle or into community life. The purpose of this study is to find out the implementation of home assimilation for inmates in 2022, and also to know the difference between the implementation of home assimilation in previous years in Sumedang Class IIB Correctional Institution. Researchers utilize qualitative research methods that are descriptive, the author uses literature data and also documentation obtained from the registration data of Sumedang Class IIB Correctional Institution. The results of this study show that the implementation of assimilation in the framework of handling covid-19 in Lapas Sumedang is in accordance with existing regulations, and the obstacles faced so far are the families of correctional residents who are not complete resulting in the inhibition of assimilation for inmates.Keywords: assimilation; correctional; covid-19; inmate.AbstrakAsimilasi rumah bagi narapidana yang sudah memenuhi berbagai persyaratan sesuai dengan Peraturan Menteri Hukum dan HAM Republik Indonesia Nomor 43 Tahun 2021 Syarat dan Tata Cara Pemberian Asimilasi, Pembebasan Bersyarat, Cuti Menjelang Bebas, dan Cuti Bersyarat, Bagi Narapidana dan Anak Dalam Rangka Pencegahan dan Penanggulangan Covid-19, bertujuan untuk membaurkan narapidana atau anak didik ke tengah-tengah atau kedalam kehidupan masyarakat. Maksud penelitian ini yaitu untuk mengetahui implementasi pemberian asimilasi rumah bagi narapidana di tahun 2022, serta juga mengetahui perbedaan diantara pelaksanaan asimilasi rumah di tahun-tahun sebelumnya di Lembaga Pemasyarakatan Kelas IIB Sumedang. Peneliti memanfaatkan metoda penelitian kualitatif yang bersifat deskriptif, penulis menggunakan data literature dan juga dokumentasi yang diperoleh dari data registrasi Lembaga Pemasyarakatan Kelas IIB Sumedang. Hasil dari penelitian ini menunjukan bahwa pelaksanaan pemberian asimilasi dalam rangka penanganan covid-19 di Lapas Sumedang sudah sesuai dengan regulasi yang sudah ada, dan hambatan yang dihadapi selama ini adalah keluarga warga binaan pemasyarakatan yang tidak lengkap mengakibatkan terhambatnya pelaksanaan asimilasi bagi narapidana.Kata kunci: asimilasi; covid-19; narapidana; pemasyarakatan.